Influence of Mulching and Weed Management Practices on Weeds and Nutrient Uptake in Greengram (Vigna rediata L.) under Eight Year Old Custard Apple Plantation - Verma, S. K.; Prasad, S. K.; Singh, S. B.; Singh, Y. V.; Singh, Ravi Prakash; Bahadur, Shiv (International Journal of Bio-resource and Stress Management, 2017)
An experiment was conducted at Agronomy Research Station, Barkacha, Mirjapur 201–14 to assess the effect of mulching and weed management practices on weeds and nutrients uptake by greengram under agri-horti system. Three mulch treatments were taken in main plot (no-mulching, dust-mulching and paddy straw-mulching) and five weed control treatments (weedy check, weed free, pendimethalin pre-emergence (PE) 1000 g ha-1, imazethapyr post-emergence (PoE) 100 g ha-1 and pendimethalin (PE) 1000 g ha-1 followed by (fb) imazethapyr (PoE) 100 g ha-1) was randomly allocated to subplots and these were replicated thrice in split plot design. The results revealed that dust mulching recorded lowest density and dry weight of weeds, N, P, K depletion by weeds and resulted significantly the highest growth parameters (pant height, crop dry weight and branches palnt-1), N, P, K content and their uptake by crop, grain and straw yield, gross and net returns of greengram over paddy straw mulching and no-mulching, respectively. Pre-emergence application of pendimethalin (1000 g ha-1) fb post-emergence application of imazethapyr (100 g ha-1) recorded lowest density and dry weight of weeds, N, P, K depletion by weeds and recorded the highest growth parameters, grain and straw yield, N, P, K contents and their uptake, gross and net returns by crop as compared to alone application of pendimethalin (PE) 1000 g ha-1 and imazethapyr (PoE) 100 g ha-1, respectively. However, no mulching recorded maximum B: C ratio in among the mulches and among weed management practices alone application of pendimethalin recorded maximum B:C ratio.